OPTIMIZATION OF INTENSIVE TECHNOLOGY-BASED BEEKEEPING SYSTEMS IN THE CONDITIONS OF THE FERGANA REGION - Mukhammadjonova Mukhlisakhon Khahramon kizi (Web of Journals Publishing, 2025)
This article scientifically studies ways to increase the efficiency of beekeeping systems based on intensive technologies in the ecological and climatic conditions of the Fergana region. The study assessed the flowering period of plants, microclimatic factors, colony strength, disease prevalence, and the effectiveness of modern technological solutions. The results show that the introduction of intensive technologies adapted to local conditions significantly improves honey yield, colony stability, and economic indicators of the farm.
Keywords: Intensive technologies, beekeeping system, colony development, feeding strategies, microclimate control, diseases and parasites.